Reducing stray corrosion in jet electrochemical milling by adjusting the jet shape - Wang, Xindi; Qu, Ningsong; Fang, Xiaolong (Journal of materials processing technology, 2019)
Jet electrochemical (Jet-EC) milling, using a movable nozzle as the cathode, can fabricate complicated structures flexibly. With the dissolution restricted to a limited area by the electrolyte jet, high removal localization and good surface quality can be obtained. However, the edge of the machined groove is usually subject to stray corrosion because of the low current density in the edge area. In this paper, it is confirmed that the jet shape, which is determined by the working parameters, has a notable influence on the edge condition. Through experiments and analysis, the interrelation between the working parameters, jet shape and edge condition in Jet-EC groove milling is established. It is found that the stray corrosion on the edge can be reduced significantly by adjusting the jet shape, and the necessary conditions to completely eliminate the stray corrosion are established. Furthermore, based on the conclusions, a groove with both a sharp edge and a smooth surface is fabricated via a two-pass process. A deep groove (1.208 mm) with a sharp edge is produced via multiple-pass milling with downward cathode feeding.